Improving the Identification Standards Mechanism for Obscene (Journal of humanities and social sciences exploratio, 2025)
The 2025 obscene figures case adjudicated by Shanghai Baoshan Court represents China's first criminal ruling classifying collectible figures as obscene materials. Current Article 367 of the Criminal Lawemploys circular definitions and subjective terminology, causing judicial determinations to rely excessively on individual adjudicators' discretion and resulting in ambiguous legal standards. Although the contested figures possessed artistic certification, their explicit design characteristics, target audience, and potential impact on minors subjected them to legal regulation—​​thus underscoring​​ the primacy of minor protection in judicial considerations. Nevertheless, substantial flaws persist in existing identification mechanisms. This study advocates for structural refinements to the obscenity determination framework to address emerging challenges posed by novel media forms, particularly represented by collectible figures.
Keywords: Identification of Obscene Materials; Protection of Minors; Criminal Judicial Standards; Legal Interest Theory